(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The physical processes of capture and ejection of charge carriers in Si-n-p radiation receivers affecting their electrophysical characteristics (voltage-current) are investigated. It is shown that after ultrasonic treatment of Si receivers, there was a decrease in the height of the potential barrier of p-n junctions formed by the presence of local clusters of impurity atoms. The result of the decay process of local clusters of impurity atoms is the smoothing of the potential relief and the uniformity of the distribution of the electric pulling field in the sensitive area of the detector.